2021
DOI: 10.1111/weng.12552
|View full text |Cite
|
Sign up to set email alerts
|

English language choices in Kazakhstan and Kyrgyzstan

Abstract: This article examines English language choice amidst dynamic social and linguistic change contexts in Kazakhstan and Kyrgyzstan. Kazakhstan has formally committed to an official trilingual language policy – Kazakh, Russian, and English. In comparison, Kyrgyzstan has a dual language policy – Kyrgyz and Russian. However, its Ministry of Education and Science has demonstrated an informal commitment to developing English competency in‐country through various English language teaching/learning initiatives. Using da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Article 14 of the Constitution promises protection of the language rights of every citizen of Kazakhstan, granting all citizens the right to use their native languages and choose their language of communication. Although language rights are protected, the minority languages are confined mostly to the community activities (Ahn & Smagulova, 2021). Being part of the former Soviet Union, Kazakhstan was deeply affected by Soviet language policy whereby Russian was highly rated and considered to offer the best opportunities for academic, political and social growth as well as being mandatory in the public administration, technical and scientific spheres.…”
Section: Sociolinguistic Changes Of Post-soviet K a Z Akhstanmentioning
confidence: 99%
“…Article 14 of the Constitution promises protection of the language rights of every citizen of Kazakhstan, granting all citizens the right to use their native languages and choose their language of communication. Although language rights are protected, the minority languages are confined mostly to the community activities (Ahn & Smagulova, 2021). Being part of the former Soviet Union, Kazakhstan was deeply affected by Soviet language policy whereby Russian was highly rated and considered to offer the best opportunities for academic, political and social growth as well as being mandatory in the public administration, technical and scientific spheres.…”
Section: Sociolinguistic Changes Of Post-soviet K a Z Akhstanmentioning
confidence: 99%
“…Moreover, despite a large number of investigations into linguistic landscapes around the world, the linguistic landscape of Kazakhstan has not received enough attention from sociolinguists. To the best of our knowledge, only two studies of the language landscape of the capital of Kazakhstan (Astana or Nur-Sultan 1 ) are known at the moment (Moore, 2014;Juan & Mukhamedzhanova, 2022). The first study, conducted in 2013, showed a significant discrepancy between the official language policy and actual practice.…”
Section: Introductionmentioning
confidence: 99%
“…The language situation in Kazakhstan is largely due to historical and geographical factors. Compared with the peripheral position during the Soviet Union, the status of Kazakh as the state language has increased significantly -a symbolic capital, giving access to political and social resources (Ahn & Smagulova, 2021). Since Kazakhstan has state borders with Russian-speaking countries, The Russian language is a powerful means of international communication.…”
Section: Introductionmentioning
confidence: 99%
“…However, learning English as a foreign language is still difficult, largely due to the lack of a language environment (Zhilbayev et al, 2019) and using outdated language teaching methods (Yeskeldiyeva & Tazhibayeva, 2015). As Ahn and Smagulova (2021) note, English in Kazakhstan remains inaccessible to the majority of the population while relatively small group was mostly accessible to a relatively small group of wealthy middle class having better access to English language resources. However, a high level of motivation to learn English as a prestigious language opens many economic (Djuraeva, 2021) and educational opportunities (Zhilbayev et al, 2019).…”
Section: Introductionmentioning
confidence: 99%